Validation of the Portuguese version of the social isolation scale with a sample of community-dwelling older adults - João Tavares; Ana Faria; Delphine Gonçalves; Diana Mendes; Sofia Silva; Liliana Sousa (Elsevier, 2023)
Objectives: The aim of this study was to analyze the psychometric properties (reliability and validity) of the Social Isolation Scale (SIS) in a sample of Portuguese community-dwelling older adults. Methods: A transversal descriptive study was carried out with a convenience sample of 250 community-dwelling older adults (≥65 years). The survey comprised a sociodemographic questionnaire, SIS, Geriatric Depression Scale-4 (GDS-4), 6-item Lubben Social Network Scale (LSNS-6), a loneliness self-assessment question, and Satisfaction with Life Scale (SWLS). Construct validity (confirmatory factor analysis) and convergent validity were analyzed, and ISI internal reliability (composite reliability), external reliability (test-retest, intraclass correlation coefficient) and inter-rater reliability (Cohen's kappa coefficient) were evaluated. Results: Confirmatory factor analysis showed a two-factor model with an excellent index of fit. The SIS showed significant correlations with LSNS-6 (rs = 0.47), SWLS (rs = 0.26), the loneliness self-assessment question (rs = 0.35), and GDS-4 (rs = −0.16). SIS composite reliability was good (0.708). The inter-class correlation coefficient varied from 0.84 to 0.98. The Cohen's kappa coefficient ranged from 0.936 to 1. Conclusions: SIS has been shown to be a valid and reliable instrument for assessing social isolation among Portuguese community-dwelling older adults. Healthcare professionals, particularly nurses working in community settings, can use SIS to assess social isolation in older adults to design, implement, and evaluate interventions.